A temporal profile of pro-abstinence-oriented constructs from the modified theory of planed behavior in a Slovenian clinical sample of treated alcoholics - an 18-year follow-up - Radovanović Mirjana; Rus-Makovec Maja (Sciendo, 2018)
Using the modified Theory of Planned Behaviour (mTPB), different indicators of therapeutic success were studied to understand pro-abstinence behavioural orientation during an 18-year after-care period following a 3-month intensive alcoholism treatment. The indicators were: perceived needs satisfaction (NS), normative differential (ND), perceived alcohol utility (UT), beliefs about treatment programme benefits (BE) and behavioural intentions (BI).